Molecular gene and regulatory profiles in thyroid cancer - Denning, Karen (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2009)
Thyroid carcinoma is the most common endocrine malignancy, with an incidence of approximately eighty cases per year in Ireland and thirty seven thousand cases per year in the United States. While thyroid cancer may be considered a relatively infrequent cancer, accounting for one percent of all cancers, world wide thyroid cancer incidences rates are increasing year after year. Furthermore thyroid nodules are a common occurrence and distinguishing benign specimens from malignant can be problematic. It is estimated that five to ten percent of individuals will develop a clinically significant thyroid nodule during their lifetime. The development of robust molecular biomarkers would significantly aid in the diagnosis of thyroid malignancy. The purpose of this thesis was to examine gene and regulatory profiles in thyroid neoplastic and inflammatory disease to evaluate their potential as molecular markers of thyroid disease. The assessment was carried out using TaqMan® RT-PCR for gene expression analysis, immunohistochemistry for protein analysis and in situ hybridisation for microRNA expression analysis.
Keywords: Histopathology and Morbid Pathology, Ph.D.; Ph.D. Trinity College Dublin